Maternal Transport. Issue 1 (January 2021) - Simpson, Kathleen Rice
Abstract : New resources about maternal transport have been published by the Association of Women's Health, Obstetric, and Neonatal Nurses and the Society for Maternal-Fetal Medicine. Details of each of the resources are reviewed with recommendations for incorporating them into clinical practice.